2011
DOI: 10.1103/physrevb.84.219903
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Exchange anisotropy pinning of a standing spin-wave mode [Phys. Rev. B83, 054405 (2011)]

Abstract: Figures 5(a) and 5(b) in this paper had an error in labeling for the with-bias and against-bias data. The following figure has been correctly labeled such that it coincides with the original caption: FIG. 5. (a) The calculated strengths of pinning p(θ = 180) along the bias direction (empty circles, solid line) and p(θ = 0) against the bias direction (empty squares, dashed line). (b) The corresponding effective magnetic thickness t eff of the NiFe along the bias direction (empty circles, solid line) and against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The static field was applied in the film plane and along the exchange-bias direction. As shown in [77], physically the exchange bias is an in-plane uni-directional interface anisotropy leading to pinning of the dynamic magnetisation at the interface of the two layers. The experiments demonstrated that when the applied field was coaligned with the exchange-bias field direction, the FMR spectra were of the type shown in the right-hand column of Fig.…”
Section: Fig 35mentioning
confidence: 97%
See 1 more Smart Citation
“…The static field was applied in the film plane and along the exchange-bias direction. As shown in [77], physically the exchange bias is an in-plane uni-directional interface anisotropy leading to pinning of the dynamic magnetisation at the interface of the two layers. The experiments demonstrated that when the applied field was coaligned with the exchange-bias field direction, the FMR spectra were of the type shown in the right-hand column of Fig.…”
Section: Fig 35mentioning
confidence: 97%
“…Similarly, every time when the applied field is along the anisotropy axis, both dynamic magnetisation components will be pinned, just for the sheer reason of the uniaxial symmetry introduced by the uniaxial anisotropy. For instance, if an IP exchange-bias field is present at one of the film surfaces and the static field is applied in the direction of the exchange bias, both components of m will be pinned/anti-pinned, although the geometry is one of the IP FMR [77].…”
Section: Fig 3 (A)mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Standing spin waves have also been used to study exchange bias as an interface pinning effect. 19 In this work, we investigate primarily using FMR the magnetic properties of a Ni 0.8 Fe 0.2 /Fe 0.5 Mn 0.5 multilayer test structure. Structural and chemical analyses show layer thickness and interface roughness variations across the sample and we are able to correlate magnetic features with specific layers, including the influence of layer position within the stack.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of an in-plane uni-directional in-plane anisotropy (exchange bias), both pinning constants are non-vanishing and depend on the direction of the exchange bias field with respect to H [23].…”
Section: Theorymentioning
confidence: 99%
“…It takes a couple of more seconds to convert the obtained Z r values into S21 by using Eqs. (18)(19)(20)(21)(22)(23)(24)(25) from [16].…”
Section: Theorymentioning
confidence: 99%